2020
DOI: 10.1093/cid/ciaa304
|View full text |Cite
|
Sign up to set email alerts
|

CYD Tetravalent Dengue Vaccine Performance by Baseline Immune Profile (Monotypic/Multitypic) in Dengue-Seropositive Individuals

Abstract: Background The immune profile of dengue-experienced individuals is a determinant of dengue reinfection severity risk. Individuals with a single prior dengue infection (monotypic) are at highest risk for severe disease, while individuals with ≥ 2 prior dengue infections (multitypic) are at lower risk. The tetravalent dengue vaccine (CYD-TDV) has shown efficacy in the prevention of dengue in individuals with prior dengue infection. We estimated efficacy in individuals with monotypic or multityp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…21 It is worth noting that the CYD-TDV vaccine confers robust efficacy against severe dengue in individuals with both a pre-vaccination monotypic and multitypic immune profile. 22 The selection of an RDT for point-of-care prevaccination screening depends on several factors, such as accuracy, ease of use, and affordability. 8,17 As well as offering high specificity and sensitivity, the OnSite IgG RDT can be done within 25 min on whole blood, and thus might facilitate convenient testing and vaccination at the same visit, increasing compliance and uptake of CYD-TDV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is worth noting that the CYD-TDV vaccine confers robust efficacy against severe dengue in individuals with both a pre-vaccination monotypic and multitypic immune profile. 22 The selection of an RDT for point-of-care prevaccination screening depends on several factors, such as accuracy, ease of use, and affordability. 8,17 As well as offering high specificity and sensitivity, the OnSite IgG RDT can be done within 25 min on whole blood, and thus might facilitate convenient testing and vaccination at the same visit, increasing compliance and uptake of CYD-TDV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously thought that monotypic individuals would benefit most from Dengvaxia, as those with multitypic immunity were expected to be protected. However, a previous study showed similar Dengvaxia efficacy in monotypic and multitypic individuals 64 . Here, we observed a significant increase WT E protein and E dimer binding, neutralizing, and EDE-like Abs in both vaccinated and unvaccinated individuals, indicating a robust boosting of the immune response in both groups.…”
Section: Discussionmentioning
confidence: 82%
“…It was previously thought that monotypic individuals would benefit most from Dengvaxia, as those with multitypic immunity were expected to be protected. However, a previous study showed similar Dengvaxia efficacy in monotypic and multitypic individuals 64 .…”
Section: Discussionmentioning
confidence: 82%
“…It should also be affordable, simple to use and provide rapid results. Two recent comparative evaluations on currently available assays showed high specificity (>98%) for all immunoassays apart from one RDT, but variable sensitivities (higher sensitivities observed for the ELISAs [89% and 93%] than the RDTs [48–71%]) [ 23 • , 24 • ] Sensitivity appeared similar in samples from individuals with recent and remote virologically confirmed dengue (VCD). Cross-reactivity to other flaviviruses was low with RDTs (</ = 7%), but more significant with ELISAs (up to 51% for West Nile and 34% for Zika).…”
Section: Vaccine Candidatesmentioning
confidence: 99%